Integration of Social Capital and Organizational Learning Theories to Improve Operational Performance - Birasnav, M.; Chaudhary, Richa; Scillitoe, Joanne (Global Journal of Flexible Systems Management, 2019)
This study focuses on integrating the premises of social capital theory and the theory of organizational learning to improve the operational performance of firms nurturing the buyer–supplier relationship. Social capital theory highlights the importance of developing social relationships between firms to create valuable resources and collectively access critical resources. Organizational learning theory highlights that the learning capacity of an organization strongly depends on top-level leaders’ behaviors, organizational structure, culture, and flexibility, and uncertainties in the environment in which the organization functions. Though many studies have focused on the impact of social capital on performance improvements in the buyer–supplier relationship, the interlinkages between social capital and organizational learning have not been given much attention. Based upon these theories, a system-focused perspective, which showcases the antecedents and outcome of the relationship between collaborative communication and learning, has been proposed in this study. A literature review has been carried out to support the linkages in the proposed conceptual model. Findings suggest that transformational buyers support creating cognitive capital with suppliers. This cognitive capital influences the structural capital, which supports improving the understanding of each party’s processes in the buyer–supplier relationship when parties have high long-term orientation. Improved learning capability reshapes organizations into flexible systems capable of responding quickly to customer requirements, and consequently, they realize a higher performance level.
Keywords: Collaborative communication; Information technology competency; Long-term orientation; Organizational learning; Supplier knowledge; Transformational leadership; dept.mgt

Green supply chain management: A theoretical framework and research directions - Birasnav, M.; Chaudhary, Richa; Henry Dunne, James; Bienstock, Joshua; Seaman, Cristina (Computers & Industrial Engineering, 2022)
Practitioners and academicians dedicate significant attention to tackling initiatives and executing mechanisms to address society’s environmental concerns. Further, organizations and researchers recognize that there is a need to implement green supply chain management (GSCM) practices as a part of green strategy. To date, embedding a sustainability dimension into supply chain management remains a challenge for organizations given the lack of systematic knowledge of the key dimensions of GSCM practices, the factors that influence the implementation of GSCM practices, and the benefits that organizations gain through the implementation of such practices. To address this problem, this study reviews 151 research articles published between 1997 and 2021 in the GSCM literature, and offers a theoretical framework that synthesizes and integrates the knowledge acquired from the reviewed literature. This framework includes various dimensions of GSCM practices identified in the past research studies, the antecedents that influence implementation of GSCM practices, and the outcomes of implementation of such practices. Further, this study offers theoretical and practical perspectives to support future research utilizing a research model as a baseline to guide organizations in the understanding of the primary GSCM attributes, their predictors, and benefits.
Keywords: Antecedents; Green supply chain; Outcomes; Systematic literature review; dept.mgt; peer-reviewed